Allegories of encounter : colonial literacy and Indian captivities - Newman, Andrew, 1968- (Published by the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia, and the University of North Carolina Press, 2019)
"Presenting an innovative, interdisciplinary approach to colonial America's best-known literary genre, Andrew Newman analyzes depictions of reading, writing, and recollecting texts in Indian captivity narratives. While histories of literacy and colonialism have emphasized the experiences of Native Americans, as students in missionary schools or as parties to treacherous treaties, captivity narratives reveal what literacy meant to colonists among Indians. Colonial captives treasured the written word in order to distinguish themselves from their Native captors and to affiliate with their distant cultural communities. Their narratives suggest that Indians recognized this value, sometimes with benevolence: repeatedly, they presented colonists with books"--